Efeito do tratamento com benzonidazol no perfil fenotípico e no padrão de citocinas leucocitárias de crianças brasileiras portadoras da forma crônicaindeterminada recente da doença de Chagas - Renato Sathler Avelar (2007)
The immune response during early human Trypanosoma cruzi infection is not completely understood, despite its role in driving the development of distinct clinical manifestations of chronic infection. Herein we report the results of a descriptive flow cytometric immunophenotyping investigation to determine the impact of Bz-treatment on major and minor peripheral blood leukocyte subpopulations in T. cruzi-infected children, characterizing the early stages of the indeterminate clinical form of Chagas disease (E-IND). Firstly, we characterized the E-IND immune profile and compared with non infected children (NI). Our results indicated significant alterations in E-IND when compared with NI, including increased values of pre-NK cells, and higher values of pro-inflammatory monocytes. The higher values of activated B lymphocytes contrasted with impaired T cell activation and the cytokinesecretion; a decreased frequency of regulatory cells was also observed. These findings reinforce the hypothesis that simultaneous activation of innate and adaptive immunity mechanisms in addition to modulation of T cell immune response occur during early events of Chagas disease. Furthermore, we favour the hypothesis that T-cell-mediated immunity,during the early indeterminate clinical form, may represent a phenomenon restricted to the cardiac and lymph node compartments, not detectable in the peripheral blood. Besides establishing the immune profile for E-IND, we evaluated the impact of Bz-treatment on thecirculating leukocytes during the early-indeterminate Chagas disease. Our results demonstrated that Bz-treatment led to higher activation status of circulating monocytes but negatively correlated with the number of IL-12+CD14+ cells. Moreover, Bz-treatment triggered high frequency of circulating pre-NK cells, besides outstanding activation status of CD16+ cells, correlated with a type-1 modulated cytokine pattern. Additionally, Bz-treatment induced substantial T and B-cell activation status associated with an overall IL-10 modulated type-1 cytokine profile. Taken together, these findings add new concepts in the context of immune activation status following the etiological treatment of Chagas disease suggesting that more than increased number of activated leukocytes in the peripheral blood, Bz-treatment may also involves a qualitative change in their functional capacity that guide their activation state toward a modulated cytokine profile that may count for the benefits of etiologicaltreatment of Chagas disease.